Electrochemical performance of highly amorphous GeOx powders synthesized in different alcohols for use in Na- and Li-ion batteries. Issue 104 (27th October 2016) - Kajita, T.; Itoh, T.
Abstract : The large particle size of amorphous powders deteriorated the cycle performance of a Na-ion cell more than that of a Li-ion cell, due to large decomposition of the electrolyte. Abstract : We synthesized highly amorphous GeO x powders by a solution synthesis method, in which NaGe was oxidized by alcohol and placed in distilled water. Further, we investigated the effect of the alcohol used during the solution synthesis method on the electrochemical Na- and Li-ion insertion/extraction performances of the powder sample. We compared the oxidation process as performed using various alcohols. The amorphous GeO x powder sample synthesized by oxidation in 2-propanol (secondary alcohol) exhibited good electrochemical performance with respect to Na- and Li-ion insertion/extraction, while the amorphous GeO x powders synthesized using methanol, ethanol, and 1-propanol (primary alcohol) showed poor performances. These powders consisted of large particles, which was the reason for their poor electrochemical performance. In particular, their cycling performance in a Na-ion cell was significantly lowered by the large particle size. Hence, during the solution synthesis process, the use of a secondary alcohol is the key to synthesizing highly amorphous GeO x powders with small particle sizes. Finally, electrolyte decomposition was also found to be one of the main causes for the deterioration of the cycling performance in a Na-ion cell, because the change in the volume of the GeO x particles during charging/discharging was smaller in the Na-ion cell than in a Li-ion cell.